Joint municipal and agricultural refuse management for Baguio City and La Trinidad - Macaranas, Esperanza M. (1985, 1985)
La Trinidad's small volume of solid wastes and suitable site and Baguio City's large volume of refuse but no suitable site for sanitary landfill make it economically and technically justifiable to have a joint solid wastes management of the two areas. The agricultural wastes of La Trinidad which are at present untreated are to be collected and disposed of together with the municipal wastes of Baguio City. Chemical analysis showed that the agricultural wastes and putrescibles of both areas have similar characteristics; the C/N ratio of which is below the optimum requirement for composting. Hence, sanitary landfill method of disposal for all the refuse is suggested in this study. The estimated annual cost of this joint management has been included in the study. Several suggestions as a cooperative venture between the private sector and the local government have likewise been offered.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Refuse and refuse disposal -- Philippines -- La Trinidad; Refuse and refuse disposal -- Philippines -- Baguio City